Management of Malignant Pleural Effusion with ASEPT® Pleural Catheter: Quality of Life, Feasibility, and Patient Satisfaction. (15th December 2016) - Dhaliwal, Inderdeep; Mahdavian, Masoud; Asghari, Shabnam; Chun To Wong, Benson; Labelle, Rosalie; Amjadi, Kayvan
Abstract : Objective . The PleurX® IPC system has been used extensively in the past. Over time, management of MPE with the PleurX system can be costly. The new ASEPT pleural catheter, through advantages in design, may ultimately show cost savings. The primary outcome of this study was to evaluate safety and efficacy of the ASEPT system. Method . This single centre, prospective study enrolled 50 patients with MPE, who were followed for as long as they were alive with a catheter. Quality of Life (QoL) was assessed before, at 2 weeks, and 6 weeks after ASEPT catheter insertion using the EORTC QLQ-C30 and LC13 questionnaires. Ease of catheter use and complications were reported by physician and community nurses. Results . 50 patients with MPE with a mean age of 64.5 ± 1.9, BDI of 2.8 ± 0.9, and ECOG score of 3.0 ± 0.7 were recruited. No immediate or long-term complications were reported during the study period. Compared to precatheter insertion, global health status (−18, p < 0.001 ), QLQ-C30 dyspnea (−39, p < 0.00001 ), and LC13 dyspnea (−11, p < 0.0005 ) significantly improved at 2 and 6 weeks after intervention. Provider surveys indicated favourable ease of use. Conclusion . The new ASEPT catheter offers a safe and effective option for the management of MPE.